THE INFLUENCE OF THE FRAUD DIAMOND PERSPECTIVE ON FINANCIAL STATEMENT FRAUD IN LPDS IN MENDOYO SUB-DISTRICT - Ni Gusti Ayu Ratih Anjelika; I Gusti Ayu Made Asri Dwija Putri, Made Yenni Latrini, I Ketut Yadnyana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to determine the influence of pressure, opportunity, rationalization and capability on financial statement fraud. This research was conducted at the LPD in Mendoyo Sub-district. The sampling method used was non-probability sampling with a purposive sampling technique, so that a total of 76 samples were obtained. The data in this study were analyzed using multiple linear regression analysis techniques using the SPSS version 25 program. The results of this study show that pressure has a negative effect on financial statement fraud, opportunity has a positive effect on financial report fraud, rationalization has no effect on financial report fraud, and capability has an effect negative on financial statement fraud. This research provides a contribution for various parties as material for consideration of factors that can influence the occurrence of fraudulent financial statements.